Reconstruction of Humanistic Social Studies Learning through a Socio-Cultural Learning Approach to Increase Students' Multicultural Awareness - Rani Maharani; Mahardika Saputra Wijaya; Nanda Pratomo Utomo (Gema Cendekia Institute, 2026)
The increasing cultural diversity of contemporary society requires educational practices that not only develop students’ cognitive competencies but also strengthen their multicultural awareness and social responsibility. This study aimed to reconstruct humanistic Social Studies learning through a socio-cultural learning approach to enhance students’ multicultural awareness. The research employed a Research and Development (R&D) design consisting of four stages: preliminary investigation and needs analysis, model design and development, expert validation and revision, and field testing and evaluation. The study involved Social Studies teachers, junior secondary school students, curriculum experts, and multicultural education specialists. Data were collected through observations, interviews, questionnaires, and document analysis, and were analyzed using qualitative and quantitative techniques. The findings revealed that existing Social Studies learning practices tended to focus on cognitive achievement and provided limited opportunities for meaningful multicultural interaction. Based on the identified needs, a reconstructed learning model was developed by integrating humanistic learning principles, socio-cultural learning theory, and multicultural education. The model consists of cultural exploration, collaborative dialogue, social inquiry, reflective interpretation, and multicultural action as its core instructional phases. Expert validation indicated that the model possessed strong theoretical relevance, instructional feasibility, and practical applicability. Field testing further demonstrated positive improvements in students’ multicultural awareness, particularly in the dimensions of cultural appreciation, tolerance, empathy, respect for diversity, and inclusive social attitudes. The study concludes that the integration of humanistic and socio-cultural perspectives in Social Studies learning provides an effective framework for fostering multicultural awareness and preparing students to participate constructively in diverse societies.